Optimizing Science Learning Outcomes Through the Use of Pop-Up Books Among Elementary School Students - Deti Permatasari; Abdul Karim; Sati (Journal of Educational Sciences, 2026)
This study was motivated by the low learning outcomes of fifth grade students in IPAS lessons at SD Negeri 1 Patalagan due to the suboptimal use of concrete and visual learning media. This study aims to determine the effect of using pop-up books on students’ learning outcomes. The study employed a quantitative approach using a pre-experimental method through a one-group pretest-posttest design. The sample consisted of 20 students selected using total sampling. Data were collected through learning outcome tests and observation sheets. The test instrument consisted of five essay questions that met the criteria for validity (calculated r > table r of 0.444), reliability (Cronbach’s Alpha of 0.761), discriminative power (corrected item-total correlation > 0.30), and difficulty level (4 questions in the moderate category and 1 in the easy category). Data analysis utilized the N-gain test and the paired t-test. The results showed that the average score increased from 66.00 to 81.25, with an N-gain value of 0.4461 (moderate category). Hypothesis testing revealed a significance value of 0.000 < 0.05, indicating that the use of pop-up books has a significant effect on students’ learning outcomes. Thus, pop-up books are effective in improving learning outcomes and creating interactive.